2003
DOI: 10.1007/s00268-002-6595-y
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Adhesion Molecules and Myocardial Injury during Coronary Artery Bypass Grafting

Abstract: Cardiopulmonary bypass is acknowledged to be one of the major causes of a complex systemic inflammatory response after cardiac surgery. Leukocyte‐endothelial binding followed by neutrophil migration appears to play a central role. These interactions are mediated by adhesion molecules on the surface of activated cells. The present study compared the perioperative levels of soluble adhesion molecules after coronary artery bypass grafting (CABG) in patients with or without cardiopulmonary bypass (CPB). Altogether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…16 It has been reported that the inflammatory reaction is involved in myocardial ischemia-reperfusion injury. 17,18 Transcardiac sICAM-1 increases significantly after aortic declamping in CABG. 8 However, our data show no correlation between sICAM-1 levels and ischemic time, CPB time, or CK-MB levels.…”
Section: Discussionmentioning
confidence: 98%
“…16 It has been reported that the inflammatory reaction is involved in myocardial ischemia-reperfusion injury. 17,18 Transcardiac sICAM-1 increases significantly after aortic declamping in CABG. 8 However, our data show no correlation between sICAM-1 levels and ischemic time, CPB time, or CK-MB levels.…”
Section: Discussionmentioning
confidence: 98%
“…These agents stimulate lipid peroxidation of endothelial cells and myocyte membranes, causing cellular dysfunction, edema and cell death [46]. CPB is associated with increased levels of soluble adhesion molecules [47]. Higher levels of adhesion molecules are briefly expressed and return to normal within a few hours but they are believed to be responsible for the dysfunction of multiple organ systems observed in the postoperative period [47].…”
Section: Discussionmentioning
confidence: 99%
“…CPB is associated with increased levels of soluble adhesion molecules [47]. Higher levels of adhesion molecules are briefly expressed and return to normal within a few hours but they are believed to be responsible for the dysfunction of multiple organ systems observed in the postoperative period [47]. A relationship between adhesion molecule expression and inflammatory mediators has also been shown [48].…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al investigated the changes in the levels of soluble adhesion molecules perioperatively (sICAM-1, sPselectin, and sE-selectin) in patients undergoing CABG surgery with or without CPB. After cardiac surgery, sP-selectin and sICAM-1 levels increased in both groups of patients being higher in the on-pump group (37).…”
Section: Adhesion Molecules In Cardiac Surgerymentioning
confidence: 84%